THE INTERPRETATION OF SURAH AL-MA’UN: AN TEMATIC STUDY - Kuthar Gabar Zedin Alle (Milenial, 2024)
This study examines the interpretation of Surah Al-Ma’un using an objective methodology aimed at shedding light on the profound meanings and lessons derived from this chapter. The study begins with an introduction to the Surah, which is one of the short Meccan chapters containing powerful messages related to social ethics and responsibility toward others. The study focuses on analyzing the vocabulary and linguistic structures in the Surah, such as the meaning of "Al-Ma’un" and its implications in the context of offering assistance and kindness to people. Additionally, it addresses the verses describing the hypocrites who outwardly display religiosity but fail to fulfill the rights of Allah and His servants, particularly in matters of prayer, honoring orphans, and helping the needy. The key conclusion of the study is that the overarching message of Surah Al-Ma’un is that denial of accountability and recompense is the root of all vile character traits and a primary cause of great sins. The Surah emphasizes the importance of honoring orphans, caring for the poor, encouraging others to do the same, being diligent in prayer, maintaining sincerity in all acts of worship, and engaging in good deeds, including offering small assistance such as lending utensils, buckets, or books. Allah (Glorified be He) condemns those who fail to perform such acts. The commentators have extracted numerous benefits from the verses of this remarkable Surah, varying in the extent of their elaboration. This study organizes and categorizes these benefits according to the order of the Surah’s verses. Among the greatest lessons of this Surah is that neglecting the rights of the Creator inevitably leads to neglecting the rights of His creation.